2019
DOI: 10.1021/acs.chemmater.8b05329
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Composition-Dependent Properties of Alloys of Cubic Halide Perovskites

Abstract: Distinct shortcomings of individual halide perovskites for solar applications, such as restricted range of band gaps, propensity of ABX 3 to decompose into AX+BX 2 , or oxidation of 2ABX 3 into A 2 BX 6 have led to the need to consider alloys of individual perovskites such as (FA,Cs)(Pb,Sn)(Br,I) 3 . This proposition creates a non-trivial material-selection problem associated with a 6-component structure, spanning a continuum of three sets of compositions (one for each sub lattice), and requiring control of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 42 publications
5
80
0
Order By: Relevance
“…the specific exchange-correlation functional used in the DFT calculations (see 'Methods') and the limited size of the used supercells. Also, thermally induced random orientations of the MA and FA molecules 44 can influence the phase diagrams. On the other hand, we expect that the observed trends in the phase diagrams are reliable, because the relative accuracies in the calculations of the free energies under I ↔ Br exchange for the investigated compounds are expected to be better than the absolute accuracies.…”
Section: Resultsmentioning
confidence: 99%
“…the specific exchange-correlation functional used in the DFT calculations (see 'Methods') and the limited size of the used supercells. Also, thermally induced random orientations of the MA and FA molecules 44 can influence the phase diagrams. On the other hand, we expect that the observed trends in the phase diagrams are reliable, because the relative accuracies in the calculations of the free energies under I ↔ Br exchange for the investigated compounds are expected to be better than the absolute accuracies.…”
Section: Resultsmentioning
confidence: 99%
“…The significantly lower ∆H f for Cs 3 Sb 2 Cl 9 translates into a much steeper change in ∆H f with respect to the Cl content in Cs 3 Sb 2 Cl y I 9−y solid solutions. Since the function relating the physical properties of (halide perovskite) alloy to its composition could exhibit 'bowing effect' originated from subtle structural relaxations, and charge transfers between ions occupying the same type of lattice sites, 36,37 we fit ∆H f (y) to the following quadratic relationship: We note that experimentally, Cs 3 Sb 2 Cl y I 9−y was found to adopt 2D structures when y is between 3.8-4, 21,35 which is in the regime where 2D structures are found to be more stable according to our theoretical results. However, Peng et al 35 also found that for y > 4, the mixed halide sample no longer existed as solid solution.…”
Section: Resultsmentioning
confidence: 99%
“…Such a behaviour is temperature independent. Qualitatively, E g (x) exhibits a 'bowing-effect' which has been widely documented for halide perovskites, 65 but the extent of bowing effects shows no strong variance across three halides. The standard deviations in E g (x, T ), which can be directly related to the strength of electron-phonon couplings, 66 did not reveal clear compositionaldependency in this case, which are indicated by the sizes of the markers in Fig.…”
Section: Composition and Temperature Dependent Electronic Dynamicsmentioning
confidence: 86%